Analisis Peleburan Aluminium 3004 Berdasarkan Jumlah Boraks dengan Metode Regresi Linear - Faddillah, Fahmi; Aldori, Yopan Rahmad; Suprapto, Suprapto (CV. IRA PUBLISHING, 2025)
This study aims to analyze the effect of borax as a flux on the melting performance of recycled 3004 aluminum from beverage can waste. The melting process was carried out using an oil-fueled furnace with six borax variations, ranging from 2.5 g to 15 g for 500 g of recycled aluminum. The results showed that the net aluminum mass increased from 209 g to 293 g, while the slag mass decreased from 242 g to 139 g. Linear regression analysis revealed a positive correlation between borax and net mass (R² = 0.9116) and a negative correlation between borax and slag (R² = 0.9135). Therefore, borax proved effective in increasing the yield of clean metal and reducing slag during the recycling of aluminum.